THE RELEVANCE OF ISLAMIC EDUCATION VALUES IN THE NOVEL “PROMISE” BY TERE LIYE (CASE STUDY OF PONDOK PESANTREN MAHASINA DARUL QUR'AN WAL HADITH) - Rohimah, Rohimah; Azzahra, Alifa Hani (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2025)
Students today need alternatives to rekindle Islamic values and education. Fostering Islamic values and education is not only carried out through formal educational institutions but can also be done through printed media such as literary works like novels. This research focuses on using novels as a learning medium in the context of Islamic educational values. The researcher chose the novel